Binding of Streptococcus pyogenes to soluble and insoluble fibronectin. - Courtney, H S (1986)
The interaction of soluble and insoluble fibronectin with Streptococcus pyogenes was investigated. Soluble fibronectin bound to S. pyogenes in a dose-dependent and irreversible manner. Lipoteichoic acid competitively inhibited the binding of fibronectin to S. pyogenes but had little effect on the binding of fibronectin to staphylococci or pneumococci. The phase of growth of the streptococci had a slight effect on binding of fibronectin, with optimal binding occurring in the late log phase. S. pyogenes cells bound to fibronectin immobilized on microtiter plates in a dose-dependent and saturable manner. Both soluble fibronectin and lipoteichoic acid inhibited the binding of streptococci to immobilized fibronectin, suggesting that streptococci interact with soluble and insoluble fibronectin in a similar manner. Antibodies to fibronectin blocked the attachment of streptococci to immobilized fibronectin, whereas normal serum had no effect. Adherence of streptococci to buccal epithelial cells was inhibited by antibodies to fibronectin, but not by normal sera or by antibodies to buccal epithelial cells. The data suggest that lipoteichoic acid on the surface of S. pyogenes binds to fibronectin exposed on the host cell and that such binding mediates the attachment of streptococci to host cells.